Carbon and nitrogen stable isotope fractionation during abiotic hydrolysis of pesticides. (December 2018) - Masbou, Jérémy; Drouin, Guillaume; Payraudeau, Sylvain; Imfeld, Gwenaël
Abstract: Compound-specific Stable Isotope Analysis (CSIA) has been recently established as a tool to study pesticide degradation in the environment. Among degradative processes, hydrolysis is environmentally relevant as it can be chemically or enzymatically mediated. Here, CSIA was used to examine stable carbon and nitrogen isotope fractionation during abiotic hydrolysis of legacy or currently used pesticides (chloroacetanilide herbicides: Acetochlor, Alachlor, S-Metolachlor and Butachlor, acylalanine fungicide: Metalaxyl, and triazine herbicide: Atrazine). Degradation products analysis and CN dual-CSIA allowed to infer hydrolytic degradation pathways from carbon and nitrogen isotopic fractionation. Carbon isotopic fractionation for alkaline hydrolysis revealed similar apparent kinetic isotope effects (AKIEC  = 1.03–1.07) for the 6 pesticides, which were consistent with SN 2 type nucleophilic substitutions. Neither enantio-selectivity (EF ≈ 0.5) nor enantio-specific isotope fractionation occurred during hydrolysis of R (AKIEC  = 1.04 ± 0.01) and S (AKIEC  = 1.04 ± 0.02) enantiomers of a racemic mixture of Metalaxyl. Dual element isotope plots enabled to tease apart CCl bond breaking of alkane (Λ ≈  ε N / ε C  ≈ 0, Acetochlor, Butachlor) and aromatic π-system (Λ ≈ 0.2, Atrazine) from CO bond breaking by dealkylation (Λ ≈ 0.9, Metalaxyl). Reference values for abiotic versus biotic SN 2 reactions derived from carbon and nitrogen CSIA may be used to untangle pesticide degradation pathways and evaluate in situ degradation during natural and engineered remediation. Graphical abstract: Highlights: CN dual-CSIA and C-ESIA revealed isotopic fractionation during pesticide hydrolysis. Significant abiotic hydrolysis of the pesticides was observed at pH ≤ 4 and ≥ 12. No enantiomeric isotopic fractionation during abiotic hydrolysis of chiral Metalaxyl. Pathway-specific carbon and nitrogen isotopic fractionation are provided.